A phenomenological ethnography of shame in the context of German criminal law. Issue 1 (1st July 2015) - Landweer, Hilge; Kozin, Alexander; Rosenmüller, Stefanie
This article seeks to contribute towards the emergent field of law and emotion by offering a multi-perspectival study that combines legal, philosophical and empirical considerations into an interdisciplinary research on shame in the German courts of lower and middle instance. On the basis of this joint theory, the study proposes the existence of law-relevant emotions, whose relevance could be argued phenomenologically and validated empirically; hence, the main claim of this study: in the courtroom emotions are communicated for specific procedural purposes. The interdisciplinary nature of the study enables us to determine the role and function of shame in an institutional setting, its relation to other emotions and, more importantly, obtain the sense of shame as it acquires a specific institutional relevance.